A shared fate: adapting and personalising medical care from the perspective of a refugee reception country - Marcin Śniadecki; Zuzanna Boyke (BMC, 2022)
Abstract The article outlines socio-medical challenges faced by a country hosting refugees. Since the full-scale Russian invasion, more than 3.6 million Ukrainians have fled to Poland. Among these, a 9-year-old post-transplant patient, Tetiana. The story of the girl and her family reveals the refugees', the authors', and other doctors' varied attitudes towards the war. Considering differences between the Polish and Ukrainian health care systems, and the need for well-coordinated and effective assistance, a professional, and realistically financed system needs to be established. The presence of Ukrainian doctors is potentially advantageous because of the shared language with Ukrainian refugees. Notwithstanding the medical community's demonstrable solidarity, the months of effort and the awareness that many people may not be helped may result in burnout. Supporting others starts with us, so that neither poor management, nor cultural differences or simple fatigue, undermine the community cohesion that Poles and Ukrainians can build together.